PENGARUH KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL DAN LOCUS OF CONTROL TERHADAP PERILAKU ETIS MAHASISWA AKUNTANSI (STUDI KASUS DI UNISRI, UNSA, UNIBA, USB DAN UTP) - Putri, Avitsah Mada Fasi; Rispantyo, Rispantyo; Widarno, Bambang (Universitas Slamet Riyadi, 2021)
The purpose of this study was to examine the Effects of EmotionalIntelligence, Spirituall.Intelligence and Locus of Control on Ethical Behavior ofAccountinggStudents. This study uses a survey method with population samplingusing perposive sampling so as to get a sample of students of the Faculty ofEconomics, University of Slamet Riyadi Surakarta (UNISRI), SurakartaUniversity (UNSA), Surakarta Batik Islamic University (UNIBA), Setia BudiUniversity (USB), and Tunas University Development (UTP). The criteria for thissample are students who have taken auditing and business ethics courses, namelythe class of 2017. Students in this study were 80 students from 318 students usingArikunto theory. The type of data used is primary data. The results of this studysimultaneously Emotional Intelligence variables significantly positive effect onEthical Behavior of. Accounting Students. Spiritual Intelligence has a significantpositive effect on the Ethical Behavior of Accounting Students. Locus of Controlhas a significant positive effect on the Ethical Behavior of Accounting Students.